Przegląd orzecznictwa Międzynarodowego Trybunału Karnego do spraw zbrodni w byłej Jugosławii: [Review of the jurisprudence of the International Criminal Tribunal for crimes in the former Yugoslavia] (Studia Prawnicze / The Legal Studies, 2003)
W niniejszej pracy została przedstawiona działalność Międzynarodowego Trybunału Karnego do spraw zbrodni w byłej Jugosławii. Autorka artykułu omówiła legalność, prymat i kompetencje rzeczową Trybunału, obowiązującą zasadę ne bis in idem w postępowaniu przed Trybunałem, środki ochrony pokrzywdzonych i świadków, uprawnienia Trybunału, tajność posiedzeń i anonimowość, formę składania zeznań. Ponadto autorka przedstawiła rozstrzygnięcia merytoryczne Trybunału w sprawach Duško Tadicia, Blaškicia, Draźena Erdemovicia, oraz Kunaraca, Vukovicia i Kovača. This paper presents the activities of the International Criminal Tribunal for crimes in the former Yugoslavia. The author of the article discussed the legality, primacy and substantive competence of the Court, the applicable principle of ne bis in idem in proceedings before the Tribunal, measures for the protection of victims and witnesses, the powers of the Tribunal, the secrecy of hearings and anonymity, the form of testimony. Furthermore, the author presented the Tribunal's substantive decisions in the cases of Duško Tadić, Blaškić, Draźen Erdemović, and Kunarac, Vuković and Kovač.